Utilization of a Pressure Sensor as a Pressure Regulator in an Autoclave Machine for Medical Equipment Sterilization and IoT-Based Monitoring - Saickoni, Mohammad; Falah, Agus Hayatal; Anshory, Izza; Wisaksono, Arief (Journal of Electrical Engineering and Computer (JEECOM), 2025)
An autoclave is a sterilization device that operates using high-pressure steam to eliminate microorganisms. However, in conventional systems, pressure regulation is still performed manually, which can lead to inconsistencies in the sterilization process and reduced effectiveness. This study developed an automatic pressure control system based on a digital pressure sensor, controlled by an Arduino Uno microcontroller and equipped with an ESP8266 module for real-time monitoring via the Internet of Things (IoT). The system also utilizes a MAX6675 temperature sensor, a solenoid valve as a pressure actuator, and an LCD as a local interface. Testing was conducted at three pressure settings (10, 15, and 25 psi) for a duration of 15 minutes. The results showed that the system was able to maintain pressure with a fluctuation tolerance of ±0.3 psi and successfully transmitted temperature and pressure data to a cloud dashboard in real-time. This system is considered effective in improving the efficiency, accuracy, and safety of the sterilization process, and has the potential to be implemented in medical and laboratory facilities.